Genetic variability of 29 Peruvian quinoa (Chenopodium quinoa Willd) accessions using AFLP markers and multivariate analysis - García-Godos, Paula (2021)
Aiming to determine the genetic variability of accessions of Chenopodium quinoa Willd. "Quinoa" from the Germplasm Bank of INIA - Ayacucho, analyze 29 accessions, which were characterized using AFLP molecular markers. The quality of the DNA extracted by the Doyle and modified Doyle method was optimal for all samples, obtaining modifications in a range of 100 - 400 ng / μl. In the standardization of the AFLP technique, it was determined that the proteins between 100 and 200 ng / μl of digested DNA were adequate to efficiently develop the AFLP technique, and it was also determined that the preamplification products that allowed the resolution amplification profiles variables were higher with a 1:4 ratio. A total of 7 primer combinations generated 220 DNA bands, being 201 polymorphic loci. Molecular data grouped the accessions into seven groups at a similarity of 0.81 ultrametric units, of which a group is made up of 23 accessions and the remaining six made up of a single accession. It was found that the mean genetic variance was 0.306 ± 0.011, with a Shannon information index of 0.463 ± 0.015, these results showed that in the 29 quinoa accessions it presents a high degree of genetic variability and there is no duplicate accession. The study determines the genetic relationship and is essential to raise the genetic improvement and conservation of quinoa.